The risk of developing autonomic dysreflexia during urodynamic testing in patients after spinal cord injury - A. A. Kamalov; D. A. Okhobotov; M. E. Chaly; M. V. Frolova; I. V. Khutoroi; R. V. Salyukov (Вестник урологии, 2023)
Introduction. Autonomic dysreflexia (AD) is a life-threatening dangerous condition in patients with spinal cord injury (SCI) above the T6 segment level. It is characterized by a sudden rise in systolic blood pressure more than 20 mmHg, and unpredictable reactions from the autonomic nervous system. An episode of autonomic dysreflexia can lead to several cardiovascular catastrophes – heart attack and/or acute cerebrovascular accident up to a lethal outcome. Currently, there is no diagnostic algorithm and no way to determine risk factors for the occurrence of autonomic dysreflexia.Objective. To search for the most informative diagnostic criteria for autonomic dysreflexia in patients with spinal cord injury.Materials and methods. The study included 40 patients with SCI above the T6 segment. Depending on the SCI degree, two groups were distinguished. Group 1 (n = 14) included patients with complete spinal cord injury, advising category A on the ASIA scale. Group 2 (n = 26) included patients with incomplete spinal cord injury, classified as ASIA-B, C, D. For a preliminary assessment of the risk factors for the development of AD, an ADFSCI questionnaire was used, then a urodynamic study was conducted with simultaneous registration of systolic / diastolic blood pressure (SBP / DBP), and heart rate, which confirmed or denied the presence of AD in patients.Results. According to the ADFSCI questionnaire, most patients showed a high degree of severity of autonomic disorders, suggesting the presence of AD. Subsequently, this assumption was confirmed by the results of a urodynamic testing with simultaneous monitoring of SBP / DBP and heart rate. When comparing the groups, statistically significant differences were found in the parameters of the ADFSCI questionnaire, as well as in the indicators of SBP / DBP (at the points of maximum detrusor pressure and when the cystometric capacity is reached).Conclusion. The obtained results allow us to draw conclusions about the high incidence of AD in patients with SCI above the T6 segment and the need for a preliminary assessment of the risks of developing this condition based on the ADFSCI questionnaire before conducting a urodynamic study. Considering the possible complications of AD, the urodynamic testing should be accompanied by continuous monitoring of the indicators of the cardiovascular system.